The Improvement of The Competency of Science Teachers Using Science KIT: Optimizing Scientific Learning - Dewi, Wahyuni Satria; Mairizwan, Mairizwan; Afrizon, Renol; Hidayati, Hidayati (Indonesian Journal of Science and Mathematics Education, 2021)
Based on observations and interviews with a science teacher at a junior high school in Pesisir Selatan Regency, it is known that there are still many science teachers who have not carried out practicum activities in scientific learning. Science kits are rarely used by teachers in science learning. The main reason is that the competence of science teachers in operating the science kit is still low. To improve the competence of science teachers in using KIT, it is very necessary to carry out activities to optimize the use of KIT for science teachers. The purpose of this study was to improve the competence of science teachers in using IPA KIT as a support for scientific learning. This type of research is a quasi-experimental design with a pretest-posttest using multiple choice test instruments at the beginning and at the end of the study. From the results of this study, it is known that there is an increase in the competence of science teachers in using science kits, with the percentage increase of 29.25%.